Curriculum Models for The Arabic Language at Markaz ‘Arabiyah Pare Course | Namādzij Al Manāhij Fī Daurah Ta’līm Al Lughah Al-‘Arabiyyah Bi Markaz ‘Arabiyyah Pare - Syakur, Abd; Ahmad, Hishomudin; Ashour, Rateb (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2023)
This research aims to determine the Arabic curriculum model at the Markaz Arabiyah Center Foundation, Pare, Kediri. In this study, researchers used a qualitative research approach with field research methods. The subjects of this study are all lecturers and students in this institution, where researchers present data obtained from observations and interviews described by data sources. This research data is from educational institutions, community environments, and community organizations. The qualitative research approach aims to understand the meaning of conditions and situations in people's social interactions. Researchers must be directly involved to understand these conditions and phenomena. Data from this study cannot be obtained by just one field entry but must be broad in observing events that occur in the field. The data collection methods in this study were interviews, observation, and documentation. While data analysis is carried out using the analysis theory proposed by Miles and Huberman, starting with data reduction, then data presentation, and finally, concluding. The result of this study is that there are at least four curriculum modules in this institution. First, The grammar curriculum, which is the Arabic learning curriculum, is classified according to grammar subjects. Second, the Situational approach to Arabic is taught according to the student's situation. Third, the Functional approach is learning according to a general function before teaching others. Fourth, Multidimensional approach, namely teaching Arabic in terms of linguistics, communication, and cultural aspects. All modules of this curriculum are integrated into the Arabia Center curriculum.